Fueling Inflamm-Aging through Mitochondrial Dysfunction: Mechanisms and Molecular Targets - Picca, Anna; Lezza, Angela; Leeuwenburgh, Christiaan; Pesce, Vito; Calvani, Riccardo; Landi, Francesco; Bernabei, Roberto; Marzetti, Emanuele (International journal of molecular sciences, 2017)
Among the complex determinants of aging, mitochondrial dysfunction has been in the spotlight for a long time. As the hub for many cellular functions, the maintenance of an adequate pool of functional mitochondria is crucial for tissue homeostasis. Their unique role in energy supply makes these organelles essential, especially in those tissues strictly dependent on oxidative metabolism. Mitochondrial quality control (MQC) is ensured by pathways related to protein folding and degradation as well as by processes involving the entire organelle, such as biogenesis, dynamics, and mitophagy. Dysfunctional MQC, oxidative stress and inflammation are hallmarks of senescence and chronic degenerative diseases. One of the consequences of age-related failing MQC and oxidative stress is the release of mitochondria-derived damage-associated molecular patterns (DAMPs). Through their bacterial ancestry, these molecules contribute to mounting an inflammatory response by interacting with receptors similar to those involved in pathogen-associated responses. Mitochondrial DAMPs, especially cell-free mitochondrial DNA, have recently become the subject of intensive research because of their possible involvement in conditions associated with inflammation, such as aging and degenerative diseases. Here, we review the contribution of mitochondrial DAMPs to inflammation and discuss some of the mechanisms at the basis of their generation.